Implementasi Pendidikan Agama Islam Sejak Usia Dini Di Era Modern - Muhammad Julian; Yesi Arikarani; Muhammad Attoriqi Hakim; Amrina Rosada; Lia Dwi Utami Dwi Utami (STAI Bumi Silampari, 2023)
Islamic education in the modern era contributes to the character and challenges of the times that precipitate charity. This article aims to create support, synergy and awareness of parents, schools and communities on the formation of children's character education from an early age. This research uses a qualitative approach using a qualitative approach with the type of library research. examine the content of the concept of Islamic education from an early age in the modern era based on information or sources of books or scientific journals from relevant literature. The results of this study conclude that the implementation of Islamic education from an early age in the modern era makes humans think, behave, act and assess all problems in accordance with Islamic guidance. AKHLAK becomes a bulwark in action to prevent this sophisticated modern impact It is necessary to strengthen the cultivation of Islamic values from an early age starting with the values of creed, morals and worship. which aims as a guideline for humans to develop character. Islamic education is supported by strategies to increase children's Islamic knowledge. Giving advice using appropriate methods in telling children with concrete examples, giving directions to children to control emotionally. To keep children from the influence of technology, restrictions on gadgets on early childhood begin with the role of parents observing the spectacle, gadgets and associations of children as a way of anticipating forming characters in the modern era.